Educação escolar entre os Kurâ-Bakairi da Terra Indígena Santana (Nobres-MT) - Surubim, Marinilza de Fátima (2017)
This research aims to describe the meanings of indigenous school education differentiated between the Kurâ-Bakairi inhabiting the Santana Indigenous Land (Nobre-MT), establishing relationships between indigenous knowledge and non-indigenous knowledge that are experienced in school daily life. The indigenous school education lives a new moment in its history that is characterized by the experience of the protagonism of the native populations of the country. These people have taken up many spaces of this institution and have seen the condition of agents and builders of a new relation with the school. In view of this context, we ask whether Indigenous School Education collaborates in the strengthening of Bakairi subjects as a group, ensuring a more decisive participation in political processes and struggles for social rights. The theoretical-methodological framework consists of the phenomenology of Merleau-Ponty (1999), Paulo Freire (1987) in the concept of education as a practice of freedom and in the interpretative anthropology of Clifford Geertz (1989). Phenomenology assumes that being forms in its relation to the other and to the world continually in a process of self-production. This study seeks to describe the phenomenon in the way it presents itself, stripped of the preconceptions of all accumulated scientific knowledge, in order to consider, first and foremost, the experience of being that experiences the phenomenon before objective reality. Based on the existing bibliography, we did interviews, we used participant observation, photographic records and informal dialogues. This research reveals that school education is highly valued among the Bakairi of the Santana Indigenous Land. Appreciation that manifests itself in the willingness of families to do what they can to enable their children to finish their studies. It is also taken as a complement to traditional education since the school is not thought of separately from the village, but as an integral part of the daily life of those who live there, collaborating in the formation of being-Bakairi-in-the-world today